2021
DOI: 10.1007/s40744-021-00349-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health-Related Quality of Life in Psoriatic Arthritis Patients: A Longitudinal Analysis

Abstract: Introduction: Psoriatic arthritis (PsA) is considered a multifaceted disease, with patients reporting low health-related quality of life (HRQoL). Data on disease burden are substantial and there exists a need for properly designed studies to learn more about the evolution of HRQoL in this condition. This study aims to identify factors associated to HRQoL evolution in PsA patients followed-up in a real-world setting in Spain. Methods: We conducted a retrospective longitudinal observational study including incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Despite the literature in other rheumatic conditions regarding the impact of IA on physical function and HRQoL, [4][5][6] there is scarce research on this area in SSc and the studies performed are in small SSc cohorts 22 or in SSc-RA overlap. 19 As such, our study adds to this area of unmet need, highlighting the significant impact that IA has on physical function and HRQoL in SSc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the literature in other rheumatic conditions regarding the impact of IA on physical function and HRQoL, [4][5][6] there is scarce research on this area in SSc and the studies performed are in small SSc cohorts 22 or in SSc-RA overlap. 19 As such, our study adds to this area of unmet need, highlighting the significant impact that IA has on physical function and HRQoL in SSc.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter, significant research has demonstrated the impact that IA has on patients' physical function and HRQoL. [4][5][6] As such, this study sought to determine the prevalence of IA in a large Australian SSc cohort and determine its treatment, disease associations, and impact on outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of PsA exerts a deleterious effect on the QoL of psoriasis patients, affecting their emotional, psychological and physical well-being. 55,56 Several studies have revealed that the considerable psychological and functional burden of PsA was similar in magnitude to those of spondyloarthritis and rheumatoid arthritis. 57,58 The DLQI focuses primarily on cutaneous involvement and does not encompass the full impact of articular disease in PsA.…”
Section: Impact Of Psa On Health-related Quality Of Life (Hrqol)mentioning
confidence: 99%
“…Spondyloarthritis (SpA) is a family of chronic inflammatory arthritides primarily targeting the joint entheses, the site of tendon or ligament insertion into bone. Enthesial inflammation can cause pain, joint damage, and loss of mobility in affected sites, leading to significant loss of quality of life ( 1 , 2 ). While in recent years there have been significant advances in the treatment of SpA, headlined by biologic treatments aimed at the blockade of tumor necrosis factor (TNF) and interleukin (IL)-17 ( 3 ); however these treatments are efficacious in only ~60% of patients ( 4 ).…”
Section: Introductionmentioning
confidence: 99%